Penerapan Program Dinamik untuk Mengoptimalkan Total Biaya dalam Perencanaan Produksi dan Pengendalian Persediaan - Bella Lestari; Sawaluddin Sawaluddin (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Dynamic programming is a mathematical technique for optimizing decisions in stages by breaking a problem inton stages mthat solve recursively. It display the quantity and arrangement of invemtory to maintain production and ,businness revenue efficiently when used in inventory control management. This production planning uses a dynamic programming method based on the results of advanced calculations start from stage  1 and move forward to stage 12. the dynamic programming approach in this writing is deterministic because the pattern of the number of requests for bread is known absolutely. Decisions involving a problem are simplified little by little rather than directly. This research uses linear regression with a mathematical formula that is:  followed by the defect percetage formula  to forecast demand for the next 12 months and apply a dynamic program to achieve the minimum total quantity.